1987
DOI: 10.1002/gj.3350220407
|View full text |Cite
|
Sign up to set email alerts
|

The nature and field relations of the Ordovician Maumtrasna Formation, County Mayo, Ireland

Abstract: The nature and lield relationships o f the Maumtrasna Formation o f the Partry Mountains. Co. Mayo, show that the formation underlies the rcgionally mappable Glenummera Formation. which is of Llanvirn age, and it is laterally equivalent to the Rosroc and Derrylea Formations. also o f Llanvirn age. The formation rests unconformably on two different volcanic domains, the hasic volcanics o f the Bohaun Volcanic Formation to the northwest (of unknown age) and the largely acidic v~lciinics and sediments of the Tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Pudsey (1984) and Williams (1984) both ascribed an alluvial fan-fan delta environment to the Mweelrea Formation. Graham (1987) suggested a similar environment prevailing during deposition of the Maumtrasna Formation despite the fact that the supposedly equivalent nearby Rosroe Formation had been interpreted as a submarine fan sequence (Archer, 1977). The implications of this revised stratigraphy for the tectonic model are detailed in Section 6 below.…”
Section: The Maumtrasna-mweelrea Formationmentioning
confidence: 91%
See 3 more Smart Citations
“…Pudsey (1984) and Williams (1984) both ascribed an alluvial fan-fan delta environment to the Mweelrea Formation. Graham (1987) suggested a similar environment prevailing during deposition of the Maumtrasna Formation despite the fact that the supposedly equivalent nearby Rosroe Formation had been interpreted as a submarine fan sequence (Archer, 1977). The implications of this revised stratigraphy for the tectonic model are detailed in Section 6 below.…”
Section: The Maumtrasna-mweelrea Formationmentioning
confidence: 91%
“…The 2 km 2 of green mudstones, informally termed the Lough Shee shales (Figure 1), conformably overlie the conglomerates of the Maumtrasna Formation and were originally assigned to the Glenummera Formation by Graham (1987). However, Harper et al (1988) correlated a trilobite fauna from the shales to trilobite species reported by Pudsey (1984), from the base of the midLlanvirn Glendavock Shale Member in the Mweelrea Formation.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the area of the Maumtrasna plateau north of Lough Nafooey, Williams (1984) has convincingly shown that the distinctive unit, ascribed by Dewey (1963) to the Maumtrasna Formation, is simply part of the Mweelrea Formation. But in the Partry Mountains area Graham (1987) maintains that the conglomerates of the Maumtrasna Formation referred to by previous workers are laterally equivalent to the Rosroe Formation of the south limb succession. It is the purpose of this paper to describe an hitherto undocumented fauna from green mudrocks in the Partry Mountains and to assess its regional significance.…”
Section: Introductionmentioning
confidence: 91%